Hematopoietic stem cell transplantation to improve prognosis in aggressive monomorphic epitheliotropic intestinal T-cell lymphoma - Min, Gi-June; Oh, Ye Eun; Jeon, Youngwoo; Kim, Tong Yoon; Kim, Byung-Su; Kwag, Daehun; Park, Sung-Soo; Park, Silvia; Yoon, Jae-Ho; Lee, Sung-Eun; Cho, Byung-Sik; Eom, Ki-Seong; et al. (Frontiers in Oncology, 2024)
IntroductionMonomorphic epitheliotropic intestinal T-cell lymphoma (MEITL) is a rare, aggressive subtype of primary gastrointestinal T-cell lymphoma. Owing to the absence of symptoms characteristic of MEITL, diagnosis can be challenging, and the low response rate to conventional chemotherapy leads to an abysmal prognosis. This study aimed to define the clinicopathologic characteristics of MEITL in Korea, evaluate the clinical outcomes of intensive chemotherapy with and without hematopoietic stem cell transplantation (HSCT), and explore prognostic factors.MethodsThis single-center retrospective study examined the clinical data of 35 patients diagnosed with MEITL at Seoul St. Mary’s Hospital from May 2012 to May 2023.ResultsWe included 22 men and 13 women (median age: 59 years; range: 37–79 years). Many patients exhibited acute abdominal pain (n=23, 65.7%) related to bowel perforation (n=21, 60.0%). Most patients (30/35, 85.7%) underwent surgical intervention to diagnose MEITL, whereas only five were diagnosed via endoscopic evaluation. Of the 32 patients receiving first-line therapy, 4 died before assessment, 10 achieved a complete response (CR), 6 had a relapse, and 18 exhibited progressive disease (PD). Seven of 10 patients received upfront HSCT, either autologous (auto-HSCT, n=4) or allogeneic (allo-HSCT, n=3). All four patients on auto-HSCT died after relapse. All three patients who received allo-HSCT maintained a CR by the final follow-up. Three of 6 patients who relapsed and 13 of 18 exhibiting PD received salvage therapy; one patient on salvage auto-HSCT with cytokine-induced killer cell infusion has survived progression free. Salvage allo-HSCT was performed on 6 of 16 patients; among them, 2 achieved a CR, 2 died after relapse, and 2 died owing to septic shock while maintaining a CR. The remaining patients, who received salvage therapy without HSCT, mostly died owing to PD. The median overall survival was 12.1 months, and the median follow-up was 33.2 months. The 1- and 5-year overall survival was 50.9% and 13.3%, respectively.DiscussionMEITL is an aggressive disease resistant to conventional therapy. Therefore, intensive chemotherapy followed by upfront allo-HSCT should be considered upon diagnosis. These findings underscore the need for novel therapeutic strategies and further investigation into optimizing treatment protocols for MEITL.